Dukungan Keluarga dan Kualitas Hidup Pasien Diabetes Mellitus yang Berobat di Puskesmas - Muhammad Jais; Teuku Tahlil; Suryane Sulistiana Susanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to examine the relationship between family support and the quality of life of DM patients. This type of research is a quantitative research using a cross-sectional design. The results showed that most DM patients (64.3%) had a good quality of life. There is a statistically significant relationship between the quality of life of patients with emotional support (p-Value = 0.0002), instrumental (p-Value = 0.0005), and informational (p-Value = 0.000), but the relationship is not significant with support award (p-Value = 0.52). In conclusion, factors related to the quality of life of DM patients are emotional, instrumental, and informational support. Keywords: Diabetes Mellitus, Family Support, Quality of Life